2015
DOI: 10.4314/ahs.v15i1.42
|View full text |Cite
|
Sign up to set email alerts
|

Idiopathic hypertrophic pachymeningitis presenting with occipital neuralgia

Abstract: Abstract:Background: Although occipital neuralgia is usually caused by degenerative arthropathy, nearly 20 other aetiologies may lead to this condition. Methods: We present the first case report of hypertrophic pachymeningitis revealed by isolated occipital neuralgia. Results and conclusions: Idiopathic hypertrophic pachymeningitis is a plausible cause of occipital neuralgia and may present without cranial-nerve palsy. There is no consensus on the treatment for idiopathic hypertrophic pachymeningitis, but the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Bosman has reported that patients with idiopathic hypertrophic pachymeningitis due to a cranial lesion can be treated using a combination therapy with methotrexate when they are refractory to glucocorticoid therapy or present with serious complications of long-term steroid therapy3). In our review of the literature, 12 patients with idiopathic hypertrophic cranial pachymeningitis was treated initially with methotrexate only or combined therapy with steroid2378101319). However, there is no report of methotrexate in the management of IHSP.…”
Section: Discussionmentioning
confidence: 98%
“…Bosman has reported that patients with idiopathic hypertrophic pachymeningitis due to a cranial lesion can be treated using a combination therapy with methotrexate when they are refractory to glucocorticoid therapy or present with serious complications of long-term steroid therapy3). In our review of the literature, 12 patients with idiopathic hypertrophic cranial pachymeningitis was treated initially with methotrexate only or combined therapy with steroid2378101319). However, there is no report of methotrexate in the management of IHSP.…”
Section: Discussionmentioning
confidence: 98%